Proton control of the lanthanoid single-ion magnet behavior of a double-decker complex with an indolenine-substituted annulene ligand - Liang, Zhifu; Damjanović, Marko; Enders, Markus (Inorganic chemistry, 2017)
Two double-decker complexes with annulene ligands functionalized with indolenine groups were synthesized and characterized. The position of the proton acting as a counterion on one of the four indolenine nitrogen atoms was determined by using DFT calculations. Deprotonation and protonation of the complex induced by adding a base and an acid, respectively, were monitored by using NMR spectroscopy. Moreover, a correlation among the degree of protonation of the complex, the opening of the hysteresis, and the slow relaxation time is discussed.